Zwischen „Erinnerungen“ und „dem Vergessen“ Ernest Renan Reloaded.: Miroslav Hroch zum 75. Geburtstag - Troebst, Stefan (Comparativ, 2009)
The founding father of comparative research on nationalism, Ernest Renan, has recently been re-discovered by a culturalist mainstream dealing with identity and memory. And indeed can his famous Sorbonne lecture of 1882 “What is a nation?“ be read as an answer to the question of “What is memory?”. The article exemplifies Renan’s influence as a theoretician of ‘memories’ (souvenirs) and ‘oblivion’ (l’oubli) by three recent texts. These are the revised and extended edition of 1991 of Benedict Anderson’s Imagined Communities. Reflections on the Origin and Spread of Nationalism, an essay by Jakob Tanner on Renan in the context of on ‘nation’, ‘communication’ and ‘memory’, published in 2001, as well as Aleida Assmann’s book of 2006 on cultures of remembrance and politics of history. As in the case of the ‘nation’ also concerning ‘memory’ Renan turns out to be an original though not systematic thinker well ahead of his time.